Fast microwave synthesis of Pt-MFI zeolite coatings on silicon micromonoliths: Application to VOC catalytic combustion - Marin, Ingrid (2012)
This paper describes the preparation of a ZSM-5 zeolite layer onto conventional Si wafers and Si micromonoliths, by using microwave-assisted seeded hydrothermal synthesis. A homogeneous ZSM-5 zeolite layer up to 680 nm was obtained over the external surface of a Si micromonolith (surface to volume ratio >300,000 m-1) after only 4 min of hydrothermal synthesis at 453 K. As a proof of concept, the catalytic activity of the prepared ZSM-5 coated micromonoliths, after a conventional Pt ion-exchange process, was demonstrated in the combustion of traces of n-hexane (200 ppmV) in air.